Pengetahuan Ibu tentang Stimulasi Dini dengan Perkembangan Motorik Halus pada Anak Usia Toddler (1-3 Tahun) - Dwi Wahyuni Botutihe; Sri Andriani Ibrahim; Cindy Puspita Sari Haji Jafar (Journal of Telenursing (JOTING), 2026)
This study aimed to determine the relationship between mothers' knowledge of early stimulation and fine motor development among toddlers aged 1–3 years at Kota Tengah Public Health Center, Gorontalo City. This study employed a quantitative method with an analytical observational design using a cross-sectional approach. The results showed a significant relationship between mothers' knowledge of early stimulation and fine motor development among toddlers aged 1–3 years (p-value = 0.001). In conclusion, there is a significant relationship between mothers' knowledge of early stimulation and fine motor development among toddlers aged 1–3 years.   Keywords: Fine Motor Development, Mothers' Knowledge, Toddler